PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STROLYLINE BERBASIS MODEL COOPERATIVE LEARNING KELAS III UPT SPF NEGERI 17 TAROWANG KABUPATEN JENEPONTO - Syam, Irmawati; Faisal, Muhammad; Usman, Hikmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted in the third grade of UPT SPF SDN 17 Tarowang, Jeneponto Regency. The purpose of this study was to develop and test the feasibility of Articualte Storyline media based on the Cooperative Learning model in third-grade civic education lessons in elementary schools. The Articualte Storyline media was designed as an active learning tool that presents material, videos, and quizzes that are relevant to students' daily lives, thereby encouraging active participation in discussions during learning. The research method used was Research and Development (R&D) with the ADDIE model, which includes thestages of Analyze, Design, Development, Implement, and Evaluate. This model was chosen because it has systematic development stages and focuses on learning needs planning, structured media planning, and continuous product development and evaluation, making it suitable for developing learning media that emphasizes feasibility and ease of use. This study focused on testing the feasibility of the media and measuring student learning outcomes. Feasibility testing was conducted through alpha testing by subject matter experts and media experts, as well as beta testing by teachers and students as media users. Data collection techniques used interviews, questionnaires, and documentation, while data analysis was conducted descriptively. The results of the study indicate that Articulate Storyline media based on the Cooperative Learning model is feasible for use as a Civic Education learning medium in third grade elementary school, in terms of content, appearance, language, and ease of use. Thus, this media can be recommended as an alternative learning medium that increases student motivation and interest in learning Civic Education.